Numerical performance of Half-Sweep Geometric Mean (HSGM) iterative method for solving third order Newton–Cotes quadrature system - Muthuvalu, M.S. (Maik Nauka-Interperiodica Publishing, 2017)
The main aim of this paper is to examine the performance of Half-Sweep Geometric Mean (HSGM) iterative method for solving large, dense, third order Newton–Cotes quadrature system associated with numerical solutions of second kind linear Fredholm integral equations. The formulation and implementation of the method are presented. Some numerical analysis are included to verify the efficiency of the method. © 2017, Pleiades Publishing, Ltd.